2013
DOI: 10.1530/jme-13-0068
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the novel duplicated PRLR gene at the late-feathering K locus in Lohmann chickens

Abstract: A partial duplication of the prolactin (PRL) receptor gene (designated as dPRLR) has been identified at the late-feathering (LF) K locus on chromosome Z of some chicken strains recently, implying that dPRLR is probably a candidate gene associated with LF development in chickens. However, little is known about the structure, functionality, and spatiotemporal expression of the dPRLR gene in chickens. In this study, using 3 0 -RACE and RT-PCR, the full-length cDNA of the dPRLR obtained from the kidneys of male Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 48 publications
(90 reference statements)
1
41
0
Order By: Relevance
“…The amino acid sequences of SOCS1a or SOCS1b genes from other species were either retrieved from GenBank or predicted according to genomic sequences. their specific ligands can activate the JAK-STAT signaling pathway, as previously reported [22,24] . However, transient expression of cSOCS1a completely inhibited the stimulatory effect of cGH-or cPRL-induced luciferase activities of Hep G2 cells.…”
Section: Functional Characterization Of Csocs1a and Csocs1b In Cultursupporting
confidence: 60%
See 2 more Smart Citations
“…The amino acid sequences of SOCS1a or SOCS1b genes from other species were either retrieved from GenBank or predicted according to genomic sequences. their specific ligands can activate the JAK-STAT signaling pathway, as previously reported [22,24] . However, transient expression of cSOCS1a completely inhibited the stimulatory effect of cGH-or cPRL-induced luciferase activities of Hep G2 cells.…”
Section: Functional Characterization Of Csocs1a and Csocs1b In Cultursupporting
confidence: 60%
“…It has been reported that SOCS1 can negatively regulate GH or PRL signaling in mammals [15,16] , therefore, in this study, we also examined whether transient expression of cSOCS1a or cSOCS1b in Hep G2 cells can block cGH/ cPRL signaling using a 5 Â luciferase reporter system, which can sensitively monitor the receptor (cGHR or cPRLR)-activated JAK-STAT signaling pathway, as reported in previous studies [22,24] . As showed in Fig.…”
Section: Functional Characterization Of Csocs1a and Csocs1b In Culturmentioning
confidence: 86%
See 1 more Smart Citation
“…These observations suggest enhanced prolactin pathway signalling as a result of the PRLR p.Leu462* mutation. An example of a functionally coupled, C-terminal PRLR mutant has recently been described in chickens, where, notably, this variant has been proposed as the causative mutation underlying a dominantly inherited feather-growth retardation phenotype 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, transcripts of the partial duplicated dPRLR were found in a wide array of tissues. Its encoded protein, a truncated version of PRLR lacking a 149-aa C-terminal tail, can be potently activated by prolatin [48], suggesting the duplicated PRLR may be involved in a wide range of physiological activities.…”
Section: Cnv and Phenotypic Variationmentioning
confidence: 99%